APPLICATION OF CRITICAL DISCOURSE ANALYSIS IN STUDYING POLITICAL POLARIZATION IN SOCIAL MEDIA - Harahap, Mhd. Harvinsyah Rozi; Sikumbang, Ahmad Tamrin; Tanjung, Ahmad Sujai (Program Pascasarjana UIN Sumatera Utara, 2026)
The development of social media as a primary digital public space has accelerated the intensity of political communication while simultaneously amplifying the symptoms of polarization in Indonesia. High internet penetration means that political discourse is not only widespread but also produced through ideologically charged language practices. This study aims to analyze how Critical Discourse Analysis (CDA) can be used to examine the construction and reproduction of political polarization on social media. The study employed a qualitative design with Fairclough's three-dimensional CDA model approach combined with van Dijk's socio-cognitive perspective. Data consisted of 150 posts and 1,200 public comments selected through purposive sampling based on indications of political content and polarization. Data were collected through digital documentation and non-participant observation, then analyzed through the stages of textual analysis, discourse practice, and social practice. The results revealed three dominant strategies in the reproduction of polarization: the dichotomization of